Contrast-enhanced ultrasound-guided radiofrequency ablation in inconspicuous hepatocellular carcinoma on B-mode ultrasound - Kim, Eui Joo; Kim, Yun Soo; Shin, Seung Kak; Kwon, Oh Sang; Choi, Duck Joo; Kim, Ju Hyun (Turkish Journal of Gastroenterology, 2017)
Abstract Background/Aims: B-mode ultrasound (US) has difficulty targeting small hepatocellular carcinomas (HCCs) with poor conspicuity during radiofrequency ablation (RFA). Contrast-enhanced ultrasound (CEUS) can improve visualization of small or inconspicuous HCCs. This study was conducted to evaluate the effectiveness of CEUS-guided RFA electrode insertion during the arterial phase in inconspicuous HCCs. Materials and Methods: Ninety-three treatment-naïve HCCs from 80 patients treated with RFA from August 2012 to December 2014 were retrospectively reviewed. Seventy-five HCCs from 65 patients underwent B-mode US-guided RFA, and 15 HCCs from 14 patients that were inconspicuous on B-mode US underwent CEUS-guided RFA during the arterial phase after injection of sulfur hexafluoride microbubbles (SonoVue®). Technical success was assessed by contrast-enhanced computed tomography within 1 week and 3 months after the procedure. Results: The mean size of HCCs treated with CEUS-guided RFA was smaller than that of HCCs treated with B-mode US-guided RFA (1.17±0.36 vs. 1.63±0.55 cm, p=0.003). Technical success rates of CEUS-guided RFA within 1 week and 3 months were 100% (15/15) and 93.3% (14/15), respectively. Technical success rates of B-mode US-guided RFA were 97.3% (73/75) and 94.5% (69/73), respectively. Conclusion: CEUS-guided RFA is highly efficacious for ablation of very small and inconspicuous HCCs. Cite this article as: Kim EJ, Kim YS, Shin SK, Kwon OS, Choi DJ, Kim JH. Contrast-enhanced ultrasound-guided radiofrequency ablation in inconspicuous hepatocellular carcinoma on B-mode ultrasound. Turk J Gastroenterol 2017; 28: 446-52.